Best practices for EHR implementation: A BC First Nations community's experience. Issue 1 (January 2020) - Wilkinson, Susi; Borycki, Elizabeth; Kushniruk, Andre
First Nations and other health leaders are looking to Electronic Health Records (EHRs) to improve the quality of health information, efficiency of health services, and health outcomes for Indigenous people in Canada. This study used qualitative and quantitative methods to identify the success factors in an EHR implementation at a First Nations health centre in British Columbia, Canada. The Best Practices EHR Implementation Framework (EHRIF) was used to analyze the success factor data and found that all of the success factors from the planning and implementation phases in the framework were important. Provincial and federal government commitment and collaboration with key stakeholders including a local physician champion were also critically important for the electronic medical record implementation to proceed. This study suggests the EHRIF can be used to promote successful EHR implementations in Aboriginal communities and can contribute to building health informatics expertise and capacity in First Nations communities.